Chloroplast Genome Analysis of Resurrection Tertiary Relict Haberlea rhodopensis Highlights Genes Important for Desiccation Stress Response - Ivanova, Zdravka; Sablok, Gaurav; Daskalova, Evelina; Zahmanova, Gergana; Apostolova, Elena; Yahubyan, Galina; Baev, Vesselin (Frontiers in Plant Science, 2017)
Haberlea rhodopensis is a paleolithic tertiary relict species, best known as a resurrection plant with remarkable tolerance to desiccation. When exposed to severe drought stress, H. rhodopensis shows an ability to maintain the structural integrity of its photosynthetic apparatus, which re-activates easily upon rehydration. We present here the results from the assembly and annotation of the chloroplast (cp) genome of H. rhodopensis, which was further subjected to comparative analysis with the cp genomes of closely related species. H. rhodopensis showed a cp genome size of 153,099 bp, harboring a pair of inverted repeats (IR) of 25,415 bp separated by small and large copy regions (SSC and LSC) of 17,826 and 84,443 bp. The genome structure, gene order, GC content and codon usage are similar to those of the typical angiosperm cp genomes. The genome hosts 137 genes representing 70.66% of the plastome, which includes 86 protein-coding genes, 36 tRNAs, and 4 rRNAs. A comparative plastome analysis with other closely related Lamiales members revealed conserved gene order in the IR and LSC/SSC regions. A phylogenetic analysis based on protein-coding genes from 33 species defines this species as belonging to the Gesneriaceae family. From an evolutionary point of view, a site-specific selection analysis detected positively selected sites in 17 genes, most of which are involved in photosynthesis (eg rbcL, ndhF, accD, atpE etc.). The observed codon substitutions may be interpreted as being a consequence of molecular adaptation to drought stress, which ensures an evolutionary advantage to H. rhodopensis.